The Role of Linguistics in the Effectiveness of Public Communication: Systematic Literature Review in the Indonesian Language Context - Husni Bt Salam; Muh. Faisal Jufry (Journal AGENCY, 2026)
Public communication plays a pivotal role in shaping social interaction, policy dissemination, and public understanding, particularly in linguistically diverse contexts such as Indonesia. This study aims to examine the role of linguistics in enhancing the effectiveness of public communication through a Systematic Literature Review (SLR). Adopting the PRISMA framework, this study analyzes 45 peer-reviewed articles published between 2021 and 2025, sourced from Scopus, Web of Science, and other reputable databases. The findings reveal that communication effectiveness is influenced by multiple interconnected linguistic dimensions, including sociolinguistics, pragmatics, discourse analysis, digital linguistics, and computational linguistics. Sociolinguistic diversity, characterized by the coexistence of Bahasa Indonesia and numerous local languages, presents both opportunities for audience engagement and challenges for message standardization. Pragmatic strategies, particularly politeness and contextual appropriateness, significantly enhance message acceptance and credibility. Additionally, discourse and framing mechanisms shape public perception by constructing meaning and influencing attitudes. The study also highlights the transformative impact of digital communication, where emerging linguistic forms increase engagement but may reduce clarity and accuracy. Furthermore, the integration of Natural Language Processing (NLP) offers promising opportunities for analyzing communication patterns, although its application in Indonesia remains limited. Overall, this study emphasizes that effective public communication requires an integrated linguistic approach that considers cultural, contextual, and technological factors. The findings provide theoretical and practical implications for researchers, policymakers, and communication practitioners.